Gamma Ray Attenuation Coefficients for Lead Oxide and Iron Oxide Reinforced In Silicate Glasses as Radiation Shielding Windows - Abbas J. Al-Saadi; Abbas K. Saadon (Ibn Al-Haitham Journal for Pure and Applied Sciences, 2017)
In this work, the mass attenuation coefficient, effective atomic number and half value layer parameters were calculated for silicate (SiO2) mixed with various levels of lead oxide and iron oxide as reinforced materials. SiO2 was used with different concentrations of PbO and Fe2O3 (25, 50 and 75 weight %). The glass system was prepared by the melt-quenching method. The attenuation parameters were calculated at photon energies varying from 1keV to 100MeV using the XCOM program (version 3.1). In addition, the mass attenuation coefficient and half value layer parameters for selected glass samples were experimentally determined at photon energies 0.662 and 1.28 MeV emitted from radioactive sources 137Cs and 22Na respectively in a collimated narrow beam geometry set-up using 2"x2" NaI (Tl) scintillation detector. These values are found to be in agreement with the values computed theoretically. Moreover, these results were also compared with those for the commercial window glass. The effective atomic number ( Zeff ) and half value layer (HVL) results indicate that  pbO+SiO2 was better gamma ray attenuation than Fe2O3+SiO2 and commercial window glass. This indicates that PbO+SiO2 glasses can be used as gamma ray shielding in replace of both of them in this energy range.